An Assessment of Emergency Department Throughput and Provider Satisfaction after the Implementation of a Scribe Program. (2nd September 2014) - Allen, Brandon; Banapoor, Ben; Weeks, Emily C.; Payton, Thomas
Abstract : Objectives. To assess the impact of a scribe program on an academic, tertiary care facility. Methods. A retrospective analysis of emergency department (ED) data, prior to and after scribe program implementation, was used to quantitatively assess the impact of the scribe program on measures of ED throughput. An electronic survey was distributed to all emergency medicine residents and advanced practice providers to qualitatively assess the impact of the scribe program on providers. Results. Several throughput time measures were significantly lower in the postscribe group, compared to prescribe implementation, including time to disposition. The left without being seen (LWBS) decrease was not statistically significant. A total of 30 providers responded to the survey. 100% of providers indicated scribes are a valuable addition to the department and they enjoy working with scribes. 90% of providers indicated scribes increase their workplace satisfaction and quality of life. Conclusions. Through evaluation of prescribe and postscribe implementation, the postscribe time period reflects many throughput improvements not present before scribes began. Scribe Program implementation led to improved ED throughput for discharged patients with further system-wide challenges needing to be addressed for admitted patients.